Rapid Aminoglycoside NP Test for Rapid Detection of Multiple Aminoglycoside Resistance in Enterobacteriaceae - Nordmann, Patrice (J Clin Microbiol, 2017)
The rapid aminoglycoside NP (Nordmann/Poirel) test was developed to rapidly identify multiple aminoglycoside (AG) resistance in Enterobacteriaceae. It is based on the detection of the glucose metabolism related to enterobacterial growth in the presence of a defined concentration of amikacin plus gentamicin. Formation of acid metabolites was evidenced by a color change (orange to yellow) of the red phenol pH indicator. The rapid aminoglycoside NP test was evaluated by using bacterial colonies of 18 AG-resistant isolates producing 16S rRNA methylases, 20 AG-resistant isolates expressing AG-modifying enzymes (acetyl-, adenyl-, and phosphotransferases), and 10 isolates susceptible to AG. Its sensitivity and specificity were 100% and 97%, respectively, compared to the broth dilution method, which was taken as the gold standard for determining aminoglycoside resistance. The test is inexpensive, rapid (<2 h), and implementable worldwide.